Soil–water characteristic curves of gap-graded soils - D'Amore, Gabriele A. R. (2013)
Soil–water characteristic curves (SWCCs) of compacted mixtures of residual soil and gravel with different particle sizes were determined from laboratory tests. The study involved compacted mixtures of 50% residual soil by dry mass and 50% gravel of different particle sizes. The compacted mixtures were gap-graded in grain–size distribution with bimodal characteristics, but their SWCCs did not exhibit a bimodal characteristic. The gap-graded nature of the grain–size distribution of the mixtures did not affect the conventional sigmoidal shapes of the SWCCs. The pore-size distribution of the mixtures indicated that large pores within the compacted mixtures were filled with fine-grained soils. The air-entry value of the compacted mixtures was found to be high due to the high dry density of the specimens. The different particle sizes of the gravel used in the mixtures resulted in a variation of air-entry value of the mixtures. The dry density and coefficient of uniformity of the grain–size distributions were found to affect the air-entry values of the mixtures and the SWCC fitting parameters n and m, respectively. The variation of SWCC fitting parameters n and m showed significant correlations between grain–size distribution and pore-size distribution of the mixtures, whereas the SWCC fitting parameter a was not the air-entry value of soil.